Al2O3-SiO2 aerogel with low cost and high specific surface area as well as preparation method and application of Al2O3-SiO2 aerogel

By mixing cheap industrial aluminum sol with SiO2 aerogel, low-cost and high specific surface area Al2O3-SiO2 aerogel is prepared, which solves the problem of performance failure of traditional aluminum-based aerogels at high temperatures and realizes the economicality of the material and performance improvement, suitable for high-temperature thermal insulation materials.

CN119160924APending Publication Date: 2024-12-20NEW MATERIAL INST OF SHANDONG ACADEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411417175.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The specific surface area of ​​the existing Al2O3 aerogels decreases sharply at high temperatures, and the porous structure collapses, resulting in performance failure. The traditional aluminum-based aerogel precursor is costly and toxic, making it difficult to realize industrialized processes.

Method used

The low-cost, high-specific surface area Al2O3-SiO2 aerogel is prepared by mixing cheap industrial aluminum sol with SiO2 aerogel through the synchronous sol method. The porosity and mechanical strength of the material are maintained using CO2 supercritical drying and high-temperature calcination processes.

Benefits of technology

It significantly reduces production costs, maintains high specific surface area and mechanical strength, simplifies production processes, improves production efficiency, achieves high temperature stability and thermal insulation performance, and promotes the wide application of aerogels in industrial and scientific research fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160924A_ABST
    Figure CN119160924A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of light nano porous materials, and particularly relates to low-cost and high-specific-surface-area Al2O3-SiO2 aerogel and a preparation method and application thereof.According to the preparation method, low-cost industrial aluminum sol is used for replacing a conventional aluminum source, so that the production cost is greatly reduced, meanwhile, the preparation process is simplified, the density of the prepared Al2O3-SiO2 aerogel is 0.11-0.23 g / cm < 3 >, and the specific surface area of the Al2O3-SiO2 aerogel is greatly increased. The prepared aerogel has the specific surface area of 302.4-698.6 m < 2 > / g, and compared with a preparation method using a traditional aluminum source, the new method has the advantages that the cost of raw materials is remarkably reduced, meanwhile, the excellent performance of the prepared aerogel in the aspects of porosity and low density is ensured, and the aerogel can be used as a high-temperature heat insulation material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lightweight nanoporous materials, and in particular relates to a low-cost and high-specific-surface-area Al2O3-SiO2 aerogel and a preparation method and application thereof. Background Art

[0002] Aerogel is a nano-scale porous solid material that is widely used due to its large specific surface area and low density. At present, the most widely used and industrialized is SiO2 aerogel, which has a specific surface area of ​​up to 1000m 2 / g. However, when the operating temperature exceeds 650℃ for a long time, SiO2 aerogel is prone to structural collapse and performance failure. Al2O3 aerogel has more outstanding high temperature resistance than SiO2 aerogel, and the operating temperature can reach 1000℃. However, during the high temperature heat treatment process, the phase composition of Al2O3 aerogel will undergo a series of changes, accompanied by changes in specific surface area. When the temperature exceeds 1000℃, the specific surface area decreases sharply, the porous structure collapses in large quantities, and the sintering phenomenon is serious, which leads to performance failure.

[0003] In the prior art, there have been a lot of studies on the composite of single Al2O3 aerogel and SiO2 aerogel, which can have a large specific surface area and greatly improve the temperature resistance. Al2O3-SiO2 aerogel is widely used in the field of thermal insulation due to its large specific surface area and excellent thermal insulation performance. The precursors of traditional aluminum-based aerogels are divided into organic and inorganic types. Common organic aluminum precursors include aluminum tert-butoxide, aluminum isopropoxide, etc. When using an organic aluminum source, the reaction process is complicated, the rates of hydrolysis and polycondensation are difficult to control, and organic alcohol salts are expensive and toxic, which will cause great damage to the environment. Common inorganic aluminum precursors include aluminum chloride, aluminum nitrate, etc. There is a large amount of Cl in the wet gel synthesized from the aluminum chloride precursor. - , it will corrode supercritical containers and pipelines, and it is impossible to form an industrial process; aluminum nitrate, the hydrolysis of nitrate ions releases a large amount of heat, and safety issues cannot be well guaranteed. Summary of the invention

[0004] The purpose of the present invention is to provide a low-cost, high-specific surface area Al2O3-SiO2 aerogel and a preparation method and application thereof, so as to overcome the shortcomings of the prior art, adopt a cheap precursor to replace the existing Al2O3 precursor, thereby reducing the cost price while maintaining the original performance of the produced product.

[0005] In order to achieve the above object, the technical solution of the present invention is:

[0006] In the first aspect, the present invention provides a low-cost and high-specific-surface-area Al2O3-SiO2 aerogel, which is composed of a mixture of Al2O3 aerogel and SiO2 aerogel, wherein the density of the Al2O3-SiO2 aerogel is 0.11-0.23 g / cm 3 , with a specific surface area of ​​302.4-698.6m 2 / g.

[0007] In some other embodiments, the mixing volume ratio of the Al2O3 aerogel to the SiO2 aerogel is 1:(1-3).

[0008] The Al2O3-SiO2 aerogel prepared by the present invention has a specific surface area similar to that of the Al2O3-SiO2 aerogel prepared by the traditional preparation process. The specific surface area of ​​the traditional Al2O3-SiO2 aerogel is about 500-700m 2 / g.

[0009] In a second aspect, the present invention provides a method for preparing the low-cost and high-specific-surface-area Al2O3-SiO2 aerogel according to the first aspect, comprising the following steps:

[0010] S1: Mix ethyl orthosilicate, deionized water and anhydrous ethanol, and seal the reaction to prepare SiO2 sol;

[0011] S2: mixing industrial aluminum sol with anhydrous ethanol, and sealing the reaction to obtain Al2O3 sol;

[0012] S3: mixing SiO2 sol and Al2O3 sol, adding a promoter, and stirring to obtain Al2O3-SiO2 composite sol;

[0013] S4: subjecting the Al2O3-SiO2 composite sol to an aging treatment to obtain an Al2O3-SiO2 composite gel;

[0014] S5: subjecting the aged Al2O3-SiO2 composite gel to CO2 supercritical drying to obtain Al2O3-SiO2 aerogel.

[0015] In some other embodiments, in step S1, the volume ratio of tetraethyl orthosilicate, anhydrous ethanol and deionized water is (5-10):(40-50):(60-80);

[0016] The conditions of the sealing reaction are: temperature of 25-50° C., stirring rate of 300-600 r / min, and stirring time of 0.25-0.6 h.

[0017] In some other embodiments, in step S2, the industrial aluminum sol is an ethanol solution with an Al2O3 concentration of 20-30wt.%;

[0018] The dosage ratio of the industrial aluminum sol and anhydrous ethanol is (12-16) g: (40-50) ml;

[0019] The conditions of the sealing reaction are: temperature of 25-50° C., stirring rate of 300-600 r / min, and stirring time of 0.25-0.6 h.

[0020] In some other embodiments, in step S3, the mixing volume ratio of the SiO2 sol and the Al2O3 composite sol is 1:(1-3);

[0021] The amount of the accelerator is 5-8 times the mass of tetraethyl orthosilicate;

[0022] In some other embodiments, in step S3, the stirring time is 5-10 min, the stirring speed is 300-600 r / min, and the temperature during the stirring process is 25-50°C.

[0023] In some other embodiments, in step S4, the aging treatment is a soaking time in anhydrous ethanol for 6-7 days, and the anhydrous ethanol is replaced every 20-25 hours.

[0024] In some other embodiments, in step S5, the CO2 supercritical drying has a drying pressure of 8-12.5 MPa, a temperature of 40-60°C, and a time of 1.5-4 h;

[0025] Alternatively, the heat treatment is high-temperature calcination using a muffle furnace: the temperature is 800-1300° C., the time is 1-1.5 h, and the heating rate is 5° C. / min.

[0026] The present invention greatly reduces the production cost by using cheap industrial aluminum sol instead of conventional aluminum source, and the Al2O3-SiO2 aerogel prepared by using cheap industrial aluminum sol has a specific surface area, excellent stability and excellent mechanical strength that are almost the same as those prepared by conventional aluminum source. The aerogel prepared by this method is not only more economically feasible, but also has excellent physical properties. Compared with the method of preparing using traditional aluminum source, the new method significantly reduces the cost of raw materials, while ensuring the superior performance of the prepared aerogel in terms of porosity and low density. In addition, this improved preparation process also simplifies the production process, improves production efficiency, and makes the large-scale production of Al2O3-SiO2 aerogel possible. The present invention not only makes a breakthrough in reducing production costs, but also shows great potential in improving material properties. Through the application of cheap industrial aluminum sol, the wide application of aerogel in various industrial and scientific research fields is further promoted.

[0027] In a third aspect, the present invention provides the use of the low-cost and high specific surface area Al2O3-SiO2 aerogel described in the first aspect in the preparation of high-temperature thermal insulation materials.

[0028] The low-cost and high-specific-surface-area Al2O3-SiO2 aerogel prepared by the present invention can still reach a specific surface area of ​​300 m after being calcined at a high temperature of 1000°C for 1 hour. 2 / g, and can still maintain 200m after calcination at 1300℃ 2 / g. This reduces its production cost and increases its output.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The present invention uses cheap industrial aluminum sol to replace conventional aluminum sources, which significantly reduces the raw material production cost. The density of the Al2O3-SiO2 aerogel with high specific surface area is 0.11-0.23 g / cm 3 , with a specific surface area of ​​302.4 to 698.6 m 2 / g, mechanical strength is 1.2~9.6MPa.

[0031] (2) The present invention adopts a synchronous sol method to prepare low-cost and high specific surface area Al2O3-SiO2 aerogel in one step. The preparation method is simple and ensures the superior performance of the prepared aerogel in terms of porosity and low density.

[0032] (3) The low-cost and high-specific-surface-area Al2O3-SiO2 aerogel prepared by the present invention can still reach a specific surface area of ​​300 m2 after being calcined at 1000°C for 1 hour. 2 / g; calcined at 1300℃, it can still maintain 200m 2 / g, has high high temperature stability and can be used as high temperature insulation material. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0034] Figure 1 This is a physical picture of the Al2O3-SiO2 aerogel material prepared in Example 1 of the present invention;

[0035] Figure 2 is a high-resolution scanning electron microscope photograph of the Al2O3-SiO2 aerogel material prepared in Example 2 of the present invention, wherein A is the Al2O3-SiO2 aerogel material after calcination, and B is the Al2O3-SiO2 aerogel material before calcination;

[0036] Figure 3 is a graph of N2 adsorption and desorption of the Al2O3-SiO2 aerogel material prepared in Examples 1-3 of the present invention;

[0037] Figure 4 This is the XRD diagram of the Al2O3-SiO2 aerogel material prepared in Example 4 of the present invention after calcination at 1300°C. DETAILED DESCRIPTION

[0038] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0039] Example 1

[0040] A method for preparing an Al2O3-SiO2 aerogel material comprises the following steps:

[0041] Add 10 ml of tetraethyl orthosilicate, 50 ml of anhydrous ethanol and 80 ml of deionized water into a beaker, seal it and stir at 600 r / min for 0.5 h to obtain SiO2 sol (solution ①).

[0042] Add 16.12 g of industrial aluminum sol and 50 ml of anhydrous ethanol into a beaker, seal it, and stir at 600 r / min for 0.5 h to obtain Al2O3 sol (solution ②).

[0043] Solution ② was slowly added into solution ①, and 42 ml of propylene oxide was added into a beaker. The mixture was stirred at room temperature for 5 minutes to obtain a binary composite sol.

[0044] The binary composite sol is allowed to stand for a period of time to allow it to fully cross-link to form a binary composite gel.

[0045] Anhydrous ethanol is poured into the binary composite gel for solvent replacement and aging. New anhydrous ethanol is replaced every 24 hours. The replacement is carried out for about 6 days so that the water in the sol is completely replaced by ethanol to obtain a binary composite alcohol gel.

[0046] The binary composite alcohol gel was placed in a CO2 supercritical drying device for drying, wherein the pressure of the drying kettle was controlled at 12.5 MPa and the temperature was set at 60°C to obtain Al2O3-SiO2 binary composite aerogel.

[0047] After testing, the density of the Al2O3-SiO2 aerogel material prepared in this embodiment 1 is 0.11g / cm 3 The specific surface area of ​​Al2O3-SiO2 aerogel is 698.6m 2 / g, and the mechanical strength is 1.2MPa.

[0048] After the Al2O3-SiO2 aerogel material prepared in Example 1 was calcined at 1000°C for 1 hour, the specific surface area could still reach 301.9 m 2 / g, and the mechanical strength is 9.4MPa.

[0049] This indicates that the Al2O3-SiO2 aerogel material prepared by the present invention has high high temperature stability and can be used as a high temperature thermal insulation material.

[0050] Figure 1 This is a physical picture of the Al2O3-SiO2 aerogel prepared in Example 1. It can be seen that a block with a columnar three-dimensional structure was successfully prepared.

[0051] Example 2

[0052] A method for preparing an Al2O3-SiO2 aerogel material comprises the following steps:

[0053] Add 7 ml of tetraethyl orthosilicate, 45 ml of anhydrous ethanol and 70 ml of deionized water into a beaker, seal it and stir at 300 r / min for 0.5 h to obtain SiO2 sol (solution ①).

[0054] Add 12.23 g of industrial aluminum sol and 50 ml of anhydrous ethanol into a beaker, seal it, and stir at 600 r / min for 0.5 h to obtain Al2O3 sol (solution ②).

[0055] Solution ② was slowly added into solution ①, and 42 ml of propylene oxide was added into a beaker. The mixture was stirred at room temperature for 5 minutes to obtain a binary composite sol.

[0056] The binary composite sol is placed in anhydrous ethanol for solvent replacement, and new anhydrous ethanol is replaced every 24 hours. The replacement is carried out for about 6 days so that the water in the sol is completely replaced by ethanol to obtain a binary composite alcohol gel.

[0057] The binary composite alcohol gel was placed in a CO2 supercritical drying device for drying, wherein the pressure of the drying kettle was controlled at 13.5 MPa and the temperature was set at 55°C to obtain Al2O3-SiO2 binary composite aerogel.

[0058] After testing, the density of the material prepared in this embodiment 2 is 0.18g / cm 3 The specific surface area of ​​Al2O3-SiO2 aerogel is 682.3m 2 / g, and the mechanical strength is 1.3MPa.

[0059] The specific surface area of ​​Al2O3-SiO2 aerogel after calcination at 800℃ for 1h is 456.1m 2 / g, and the mechanical strength is 3.2MPa.

[0060] Figure 2 is a high-resolution scanning electron microscope photograph of the Al2O3-SiO2 aerogel material prepared in Example 2. Figure 2 (A) is an enlarged view of the Al2O3-SiO2 aerogel material after calcination. It can be seen that the two materials Al2O3-SiO2 are evenly distributed in the aerogel; Figure 2 (B) is an enlarged image before calcination, from which the porous characteristics of the aerogel can be clearly seen. The overall state is the classic chain bead structure of the aerogel, which proves that the Al2O3-SiO2 aerogel was successfully prepared.

[0061] Example 3

[0062] A method for preparing an Al2O3-SiO2 aerogel material comprises the following steps:

[0063] Add 5 ml of tetraethyl orthosilicate, 40 ml of anhydrous ethanol and 60 ml of deionized water into a beaker, seal it and stir at 300 r / min for 0.5 h to obtain SiO2 sol (solution ①).

[0064] Add 14 g of industrial aluminum sol and 40 ml of anhydrous ethanol into a beaker, seal it, and stir at 600 r / min for 0.5 h to obtain Al2O3 sol (solution ②).

[0065] Solution ② was slowly added into solution ①, and 42 ml of propylene oxide was added into a beaker. The mixture was stirred at room temperature for 5 minutes to obtain a binary composite sol.

[0066] The binary composite sol is placed in anhydrous ethanol for solvent replacement, and new anhydrous ethanol is replaced every 24 hours. The replacement is carried out for about 6 days so that the water in the sol is completely replaced by ethanol to obtain a binary composite alcohol gel.

[0067] The binary composite alcohol gel was placed in a CO2 supercritical drying device for drying, wherein the pressure of the drying kettle was controlled at 14.5 MPa and the temperature was set at 65°C to obtain Al2O3-SiO2 binary composite aerogel.

[0068] After testing, the density of the material prepared in this embodiment 3 is 0.23g / cm 3 The specific surface area of ​​aerogel is 589.7m 2 / g, and has a mechanical strength of 1.4MPa.

[0069] The specific surface area of ​​Al2O3-SiO2 aerogel after calcination at 1000℃ for 1h is 302.4m 2 / g, and has a mechanical strength of 9.6MPa.

[0070] Figure 3This is the N2 adsorption-desorption curve of the Al2O3-SiO2 aerogel material prepared in Example 1-3. The hysteresis loop shows that part of the composite material exhibits the characteristics of a mesoporous material.

[0071] Example 4

[0072] A method for preparing an Al2O3-SiO2 aerogel material comprises the following steps:

[0073] Add 6 ml of tetraethyl orthosilicate, 55 ml of anhydrous ethanol and 58 ml of deionized water into a beaker, seal it and stir at 300 r / min for 0.5 h to obtain SiO2 sol (solution ①).

[0074] Add 13 g of industrial aluminum sol and 55 ml of anhydrous ethanol into a beaker, seal it, and stir at 600 r / min for 0.5 h to obtain Al2O3 sol (solution ②).

[0075] Solution ② was slowly added into solution ①, and 42 ml of propylene oxide was added into a beaker. The mixture was stirred at room temperature for 5 minutes to obtain a binary composite sol.

[0076] The binary composite sol is placed in anhydrous ethanol for solvent replacement, and new anhydrous ethanol is replaced every 24 hours. The replacement is carried out for about 6 days so that the water in the sol is completely replaced by ethanol to obtain a binary composite alcohol gel.

[0077] The binary composite alcohol gel was placed in a CO2 supercritical drying device for drying, wherein the pressure of the drying kettle was controlled at 12 MPa and the temperature was set at 50°C to obtain an Al2O3-SiO2 binary composite aerogel.

[0078] After testing, the density of the material prepared in Example 4 is 0.17 g / cm 3 , with a specific surface area of ​​563.2m 2 / g.

[0079] Figure 4 This is the XRD pattern of the Al2O3-SiO2 aerogel material prepared in Example 4. It can be seen in the figure that the Al2O3-SiO2 aerogel prepared after calcination at 1300℃ for 1.5h has γ-Al2O 3, This proves that the prepared Al2O3-SiO2 aerogel is a typical aluminum-based aerogel crystal form.

[0080] Comparative Example 1

[0081] The difference from Example 1 is that aluminum chloride is used instead of industrial aluminum sol to prepare Al2O3 sol; the other preparation processes are exactly the same as those in Example 1.

[0082] The density of the prepared Al2O3-SiO2 aerogel was tested to be 0.12 g / cm 3 , with a specific surface area of ​​602.3m 2 / g, and the mechanical strength is 1.2MPa.

[0083] The specific surface area of ​​Al2O3-SiO2 aerogel after calcination at 1000℃ for 1h is 312.6m 2 / g, mechanical strength is 7.6MPa,

[0084] Comparative Example 2

[0085] The difference from Example 1 is that a small amount of propylene oxide is added when the Al2O3 aerogel and the SiO2 aerogel are mixed; the other preparation processes are exactly the same as those in Example 1.

[0086] The density of the prepared Al2O3-SiO2 aerogel was tested to be 0.18 g / cm 3 , with a specific surface area of ​​612.4m 2 / g, and the mechanical strength is 0.8MPa.

[0087] The specific surface area of ​​Al2O3-SiO2 aerogel after calcination at 1000℃ for 1h is 264.5m 2 / g, and the mechanical strength is 2.2MPa.

[0088] Comparative Example 3

[0089] The difference from Example 1 is that the binary complex alcohol gel is dried at normal pressure at a drying temperature of 75-100° C.; the other preparation processes are exactly the same as those of Example 1.

[0090] The density of the prepared Al2O3-SiO2 aerogel was tested to be 0.23 g / cm 3 , with a specific surface area of ​​164.3m 2 / g, and the mechanical strength is 3.2MPa.

[0091] The specific surface area of ​​Al2O3-SiO2 aerogel after calcination at 1000℃ for 1h is 112.8m 2 / g, and the mechanical strength is 8.8MPa.

[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A low-cost, high-surface-area Al 2 O 3 -SiO 2 Aerogel, It is characterized in that By Al 2 O 3 Aerogel and SiO 2 Aerogel mixed composition, the Al 2 O 3 -SiO 2 The density of aerogel is 0.11-0.23g / cm 3 , with a specific surface area of ​​302.4-698.6m 2 / g.

2. The low-cost and high-specific-surface-area Al according to claim 1 2 O 3 -SiO 2 Aerogel, It is characterized in that The Al 2 O 3 Aerogel and SiO 2 The mixing volume ratio of aerogel is 1:(1-3).

3. A low-cost and high-specific-surface-area Al according to claim 1 or 2 2 O 3 -SiO 2 Method for preparing aerogel, It is characterized in that The following steps are involved: S1: Mix ethyl orthosilicate, deionized water and anhydrous ethanol, and seal the reaction to obtain SiO 2 Sol; S2: Mix industrial aluminum sol with anhydrous ethanol and seal the reaction to obtain Al 2 O 3 Sol; S3: SiO 2 Sol and Al 2 O 3 Sol is mixed, accelerator is added, and Al is obtained by stirring. 2 O 3 -SiO 2 Composite sol; S4: Al 2 O 3 -SiO 2 The composite sol was aged to obtain Al 2 O 3 -SiO 2 Composite gel; S5: The aged Al 2 O 3 -SiO 2 Composite gel for CO 2 Supercritical drying to obtain Al 2 O 3 -SiO 2 Aerogel.

4. The preparation method according to claim 3, It is characterized in that In step S1, the volume ratio of tetraethyl orthosilicate, anhydrous ethanol and deionized water is (5-10):(40-50):(60-80); The conditions of the sealing reaction are: temperature of 25-50° C., stirring rate of 300-600 r / min, and stirring time of 0.25-0.6 h.

5. The preparation method according to claim 3, It is characterized in that In step S2, the aluminum content of the industrial aluminum sol is 20%-30wt.%. The dosage ratio of the industrial aluminum sol and anhydrous ethanol is (12-16) g: (40-50) ml; The conditions of the sealing reaction are: temperature of 25-50° C., stirring rate of 300-600 r / min, and stirring time of 0.25-0.6 h.

6. The preparation method according to claim 3, It is characterized in that In step S3, the SiO 2 Sol and Al 2 O 3 The mixing volume ratio of the composite sol is 1:(1-3); The amount of the accelerator is 5-8 times the mass of tetraethyl orthosilicate; 7. The preparation method according to claim 3, It is characterized in that In step S3, the stirring time is 5-10 min, the stirring speed is 300-600 r / min, and the temperature during the stirring process is 25-50°C.

8. The preparation method according to claim 3, It is characterized in that In step S4, the aging treatment is performed by soaking in anhydrous ethanol for 6-7 days, and the anhydrous ethanol is replaced every 20-25 hours.

9. The preparation method according to claim 3, It is characterized in that In step S5, the CO 2 The drying pressure of supercritical drying is 8-12.5MPa, the temperature is 40-60℃, and the time is 1.5-4h; 10. A low-cost and high-specific-surface-area Al as claimed in claim 1 or 2 2 O 3 -SiO 2 Application of aerogel in the preparation of high temperature thermal insulation materials.